THE EFFECT OF AIR DRYING TIME ON BONDING (SELF ETCH) WITH ETHANOL AS A SOLVENT TO THE SHEAR BOND STRENGTH OF BIOACTIVE COMPOSITE RESIN - Devi Rosalinda; Dewi Puspitasari; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2021)
ABSTRACTBackground: Surface resistance between composite resin and dentin is currently one of the problems of restorative materials. Failure ofcomposite resin are still being reported in clinical studies with failure rates ranging between 5-45% based on observations for 5-17 years. Bioactive composite resin is a new type of composite resin that has mechanical and chemical properties similiar to teeth. The use of resins, bonding materials, drying time of the solvent, and type of solvent also affect the shear bond strength Purpose: The purpose of this study was to analyze the effect of air drying time bonding (self-etch) with ethanol as a solvent on the shear bond strength of bioactive composite resins. Methods: This study used 32 non-carious maxillary premolar teeth that were fixed using acrylic resin. Fiber glass with a diameter of 3 mm and thickness of 3 mm were fixed to dentin surface and applied using bioactive composite resin were divided into 4 treatment group, i.e. the group without air drying, 20 s, 40 s, and 60 s. Shear bond strength test using Universal Testing Machine. Results: One Way Anova and Post Hoc Bonferroni test showed significant differences with p=0,002 (p<0,05). The average shear bond strength value of the lowest bioactive composite resin in the group bonding without air drying with a value of 6.381 ± 2.818 MPa and the highest shear bond strength value of the bioactive composite resin in the 60 seconds bonding air drying group with a value of 11.873 ± 2.931 MPa. Conclusion: The air drying time of the bonding affects the shear bond strength of the bioactive composite resin.Keywords: Air drying time, bioactive composite resin, bonding, ethanol, shear bond strength.